Ecologyphytocoenotic characteristic of Ferula foetida (Bunge) of Regel. inMangyshlak desert assosiations (Eurasian Journal of Ecology, 2018)
The purpose of this research was to find out ecology- phytocenotic characteristics of Ferula foetidain various habitats of Mangystau region. The specific structure, soil features, participation in community, abundance of Ferulafoetidawas studied for 10 cenopopulations. Haloxylonaphyllum – Ferulafoetida – Artemisiasanltolina, Ferulafoetida – Herbaxerophytica – Haloxylonaphyllum, Haloxylonaphyllum – H.persarum – Ferulafoetida – Krascheninnikowiaceratiodes, Haloxylonpersicum – Artemisiasantolina – Herbaxerophytica– Ferulafoetida, Artemisiakemrudica – Ferulafoetida – Herbaxerophytica–Haloxylonpersarum, Carexphysodes – Artemisiasantolina – Art.kemrudica– Ferulafoetida – Haloxylonpersium, Artemisiaterrae-albae – Ferulafoetida– Anabasissalsa, Artemisiaterrae-albae – Ferulafoetida – Arthrophytumlehmannianum, Artemisiaterrae-albae – Art.arenaria – Ferulafoetida – Haloxylonpersium – Calligonumleucocladum, Artemisia terrae-albae – Ferula foetida– Agropyron fragile. It is defined that in all researched communities Ferulafoetidacan be included in both lower herbaceous vertical (at virginile period)and medium shrubby-herbaceous (at generative period) layers. Communitieswith Ferula foetidacould successfully formed on various types of soils by theirmechanical composition – from sandy to loamy-stony.Key words: Ferula foetida, Mangyshlak, abundance, spread, floristiccomposition, cenopopulation, ecology.